Effect of Unfiltered Coffee on Carbon Tetrachloride-Induced Liver Injury in Rats - Poyrazoglu, Orhan Kursat; Bahcecioglu, Ibrahim Halil; Ataseven, Huseyin; Metin, Kerem; Dagli, Adile Ferda; Yalniz, Mehmet; Ustundag, Bilal (Springer/Plenum Publishers, 2008)
To assess the role of unfiltered coffee upon carbon tetrachloride (CCl(4)) induced hepatotoxicity in rats. All rats were randomly divided into control group, CCl(4)-treated, unfiltered coffee-treated and CCl(4)/unfiltered coffee-treated. Hepatic damage was induced by repeated intraperitoneal injections of CCl(4) every other day. Unfiltered coffee was given as drinking fluid for 8 days starting the day before CCl(4) administration. Liver enzymes, plasma and liver tissue malondialdehyde were analyzed. Histopathological evaluation of liver sections was performed. Serum aminotransferase level significantly increased in CCl(4)/unfiltered coffee-treated group compared to CCl(4)-treated group, as well as, lipid peroxidation products in the plasma and liver tissue. In addition, histopathological findings including inflammation and necrosis were significantly confirmed these findings. Unfiltered coffee potentiates acute liver injury in rats with CCl(4)-induced hepatotoxicity.
Keywords: coffee; acute liver injury; carbon tetrachloride; lipid peroxidation